Estudo e análise cinética do processo fermentativo do vinho tinto com maturação da uva Isabel em barril de cavalho - Mendonça Júnior, Francisco Edézio de (Universidade Federal Rural do Semi-Árido, 2018)
Wine is one of the most well-known and consumed drinks in the world, due to its great and specialty. The earliest sales of mankind and its inspiration are still very current, due to a still very remote time period with respect to evidence. The production process is used in several steps and use of it as its main input. The procedure for artisanal production encompasses a few steps is the main one of the industrial process. It is promoted by the crushing of the grape to the formation of the must which is the bagasse, pulps and seeds. Soon afterwards, juice and must are incubated for the first fermentation phase to occur, with the conversion of most sugars and tannin extraction and color, and then strained and transferred to a complementary fermentation tank where the wine is ready. After some adjustment and analysis, the product is ready to be emptied. The kinetics of radiation are the same as the signals, which are they are those are there are signals at the error and their wave signals are behavior at the bohemian and gravity analyzer model Brix and Gravity direction; a concentration of sugar, which in turn is linked to the alcohol content; a concentration of inoculum of yeast, being this great resistance of the biochemical of yeast; and a wave intensity that promotes mass distribution and thermal equilibrium of the medium. The present work is to perform a kinetic analysis of the reaction of red wine handmade Isabel water, demonstrating that each stage of production and how it is able to combat the chemistry of alcoholic formation.
Monografia
Keywords: Vinho; Inoculo; Tanino; Cinética; Wine; Inoculum; Tannin; Kinetics; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA